1991
DOI: 10.1128/aem.57.8.2186-2191.1991
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of Protein and Model Dipeptide Substrates by Attached and Nonattached Marine Pseudomonas sp. Strain NCIMB 2021

Abstract: Rates of substrate hydrolysis by nonattached bacteria and by bacteria attached to particles derived from marine diatom frustules were estimated by using two substrates, a dipeptide analog and a protein. Adsorption of the two substrates onto the particles was also evaluated. Methyl-coumarinyl-amide-leucine (MCA-leucine) was used to estimate hydrolysis of dipeptides by measuring an increase in fluorescence as MCA-leucine was hydrolyzed to leucine and the fluorochrome methylcoumarin. To examine hydrolysis of a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Previous studies have shown that when cells attach to a surface they undergo physiological and metabolic changes ( Davies & McFeters 1988; McFeters et al . 1990 ; Griffith & Fletcher 1991; Davies, Chakrabarty & Geesey 1993; Vandevivere & Kirchman 1993; Ascon‐Cabrera, Ascon‐Reyes & Lebeault 1995; Wentland et al . 1996 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that when cells attach to a surface they undergo physiological and metabolic changes ( Davies & McFeters 1988; McFeters et al . 1990 ; Griffith & Fletcher 1991; Davies, Chakrabarty & Geesey 1993; Vandevivere & Kirchman 1993; Ascon‐Cabrera, Ascon‐Reyes & Lebeault 1995; Wentland et al . 1996 ).…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced as well as diminished rates of hydrolysis, remineralization, and bacterial growth have been reported for OM bound to seston, sediments, sediment surrogates, and soils (e.g. Dashman and Stotsky 1986;Griffith and Fletcher 199 1;Smith et al 1992;Mayer 1994). Whether sorbed OM is degraded or preserved will depend on the age, location, and structure of the material.…”
mentioning
confidence: 99%
“…The interactions between attached bacteria and adsorbed nutrients have been well documented [1, 2, 23–33], but the results of those studies give an inconsistent picture of what occurs when both bacteria and nutrient become immobilised at a solid–liquid surface. In some cases the adsorption of nutrients resulted in recalcitrance of an otherwise readily biodegradable substrate [26, 31], whereas the study of Griffith and Fletcher [2] reported that attached bacteria benefited from nutrients adsorbed to a common surface.…”
Section: Discussionmentioning
confidence: 99%
“…Among the molecules which would be expected to have a higher chemical activity as a result of adsorption are the amphipathic or surface‐active agents, and in 1943 ZoBell [1] reported that bacteria benefited from access to a greater surface area when utilisable surfactants were present. The work of Griffith and Fletcher [2] on the hydrolysis of a low molecular weight dipeptide methylcoumarinylamide leucine (MCAL) and bovine serum albumin (BSA) by attached and non‐attached bacteria has shown the same phenomenon, in that BSA adsorbed to a test adsorbent much more than did MCAL, and was hydrolysed four times faster by bacteria which were attached compared with non‐attached cells. This observation enforces the view that attached bacteria may derive an advantage from being attached when they are metabolising molecules that adsorb to the surface.…”
Section: Introductionmentioning
confidence: 99%